1998
DOI: 10.1021/bi9812221
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Utility of an RNA-Cleaving DNA Enzyme

Abstract: We previously reported the in vitro selection of a general-purpose RNA-cleaving DNA enzyme that exhibits a catalytic efficiency (kcat/KM) exceeding that of any other known nucleic acid enzyme [Santoro, S. W. and Joyce, G. F. (1997) Proc. Natl. Acad. Sci. U.S.A. 94, 4262-4266]. This enzyme contains approximately 30 deoxynucleotides and can cleave almost any RNA substrate under simulated physiological conditions, recognizing the substrate through two Watson-Crick binding domains. The kinetics of cleavage under c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
496
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 419 publications
(533 citation statements)
references
References 47 publications
36
496
1
Order By: Relevance
“…Two kinds of catalytic DNA sequences, RNA-cleaving DNAzyme (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) 26,27 and G-quadruplex horseradish peroxidase-mimicking DNAzyme (PW17) [28][29][30] were applied in our research. The 10-23 RNAcleaving DNAzyme has been reported to cleave any purinepyrimidine (RY) junction under simulated physiological conditions 26 ; hence, it was applied in our strategy for the cleaving of target RNA molecule to initiate the following exponential amplification.…”
mentioning
confidence: 99%
“…Two kinds of catalytic DNA sequences, RNA-cleaving DNAzyme (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) 26,27 and G-quadruplex horseradish peroxidase-mimicking DNAzyme (PW17) [28][29][30] were applied in our research. The 10-23 RNAcleaving DNAzyme has been reported to cleave any purinepyrimidine (RY) junction under simulated physiological conditions 26 ; hence, it was applied in our strategy for the cleaving of target RNA molecule to initiate the following exponential amplification.…”
mentioning
confidence: 99%
“…As shown in Figure 3, DZ7 effectively cleaved b-gal RNA to produce the products with the expected sizes (650 nt and 300 nt) ( Figure 3). It has been reported that the 10-23 DNA enzyme is almost completely intolerant of sequence changes within the catalytic domain 7 and a single substitution from T to G in the catalytic domain of DNA enzyme abolishes target RNA cleavage activity. 17 As shown in Figure 3, DZ7m with the same substitution had no cleavage activity.…”
Section: Construction Of the Pssxe Ssdna Expression Vectormentioning
confidence: 99%
“…One such catalytic ODN referred as 10-23 DNA enzyme has the potential to cleave almost any RNA target containing purine-pyrimidine junctions. 6,7 This 10-23 DNA enzyme, isolated by in vitro selection using a combinatorial ODN library, consists of a 15 deoxynucleotide catalytic domain flanked by two target RNA-binding domains of seven or eight deoxynucleotides each. 6,7 Unlike antisense ODNs that mainly rely on cellular Ribonuclease H activity to destroy target mRNA, the 10-23 DNA enzyme is responsible for both target recognition and cleavage of target mRNA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations